2020
DOI: 10.1186/s41687-020-00243-4
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of the patient enablement instrument (PEI) after GP appointments in Finnish health care centres

Abstract: Background The aim of this study was to assess the validity and reliability of the Patient Enablement Instrument (PEI) in Finnish health care centre patients. A pilot study was conducted to assess the content validity of the PEI. A questionnaire study in three health care centres in Western Finland was performed in order to assess acceptability, construct validity, internal consistency, and measurement error of the instrument. A telephone interview 2 weeks after the appointment was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Scores of 6–7 are considered acceptable and the mean score was 6.5. Scores were higher than reported in other studies who reported lower mean scores of between 3 and 4 ( 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 87%
“…Scores of 6–7 are considered acceptable and the mean score was 6.5. Scores were higher than reported in other studies who reported lower mean scores of between 3 and 4 ( 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 87%
“…The issue was identified when previous authors evaluated test-retest reliability for PEI, finding this to be a relatively weak psychometric property, as PEI scores diminished over a 2 week period after consultation. 22,23 In a study comparing PEI against two established satisfaction measures following primary care consultations, PEI scores were much lower. The authors concluded that enablement is a distinct construct to satisfaction and the two may not correlate.…”
Section: Patient Enablement Indexmentioning
confidence: 99%
“…Responses are given a score based on a Likert scale ranging from "much better" (2), "better" (1), "same or less" (0) and "not applicable" (0). The maximum score is 12 [25].…”
Section: The Peimentioning
confidence: 99%